2023
DOI: 10.3389/fonc.2023.1122110
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the roles and clinical potential of YY1 in the tumor microenvironment

Abstract: Yin-Yang 1 (YY1) is a member of the GLI-Kruppel family of zinc finger proteins and plays a vital dual biological role in cancer as an oncogene or a tumor suppressor during tumorigenesis and tumor progression. The tumor microenvironment (TME) is identified as the “soil” of tumor that has a critical role in both tumor growth and metastasis. Many studies have found that YY1 is closely related to the remodeling and regulation of the TME. Herein, we reviewed the expression pattern of YY1 in tumors and summarized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 135 publications
0
10
0
Order By: Relevance
“…Upon conducting a Venn analysis on the predicted VDBP transcription factors from the Cistrome database, the VDR interacting proteins identified by MS, and the VDR interacting proteins in the FPClass database, the presence of Yin-Yang 1 (YY1) was found (Figure 6 B). YY1, belonging to the GLI-Kruppel family of transcription factors, acts as a DNA binding protein and is involved in numerous biological processes, including cell growth, embryonic development, transcriptional regulation, and tumorigenesis 31 , 32 . The interaction between the VDR and YY1 was validated through Co-IP and PLA experiments, and an increase in their interaction was observed with an increase in VD dosage (Figure 6 C-D).…”
Section: Resultsmentioning
confidence: 99%
“…Upon conducting a Venn analysis on the predicted VDBP transcription factors from the Cistrome database, the VDR interacting proteins identified by MS, and the VDR interacting proteins in the FPClass database, the presence of Yin-Yang 1 (YY1) was found (Figure 6 B). YY1, belonging to the GLI-Kruppel family of transcription factors, acts as a DNA binding protein and is involved in numerous biological processes, including cell growth, embryonic development, transcriptional regulation, and tumorigenesis 31 , 32 . The interaction between the VDR and YY1 was validated through Co-IP and PLA experiments, and an increase in their interaction was observed with an increase in VD dosage (Figure 6 C-D).…”
Section: Resultsmentioning
confidence: 99%
“…Cyclooxygenase 2 (COX-2), an enzyme associated with inflammatory responses, is another mediator in the regulation of PD-L1 by YY1. YY1 binds directly to the COX-2 promoter, positively regulating its expression in inflammatory contexts [ 155 , 156 ]. In vitro, inhibition of COX-2 was shown to downregulate PD-L1 expression in melanoma cells [ 157 ].…”
Section: Regulation Of Pd-l1 By Yy1mentioning
confidence: 99%
“…There is significant current evidence regarding the impact of YY1 regulation of PD-L1 in several cancers. Multiple studies have implicated the YY1/PD-L1 axis in immune escape in melanoma, NSCLC, liver cancer, and lymphoma [ 47 , 156 ]. It has been determined that YY1 is an important regulator of PD-L1 during T-cell exhaustion and promotes immune escape in prostate cancer [ 115 , 208 , 212 ].…”
Section: Overall Perspectives and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has shown that the tumor suppressor p53 (TP53) is a regulator of PPP, as it can inhibit the expression of glucose transporters (GLUT1 and GLUT4). Therefore, TP53 could deprive cancer cells of glucose, the primary substrate for PPP [ 60 63 ]. Fahong Wu et al [ 33 ] found that ELFN1-AS1 promotes G6PD activity by inducing the degradation of TP53 protein in CRC.…”
Section: Elfn1-as1 Mechanism Of Action In Cancermentioning
confidence: 99%